Deutschlands Politik gegenüber der Belt and Road Initiative der Volksrepublik China 2013-2018: eine erste Bestandsaufnahme - Harnisch, Sebastian (Asien, 2018)
The article describes and explains Germany’s societal, economic, and political reactions to the “Belt and Road Initiative” (BRI). This is (potentially) China’s global interconnectivity platform, established in 2013 to address development challenges in some of the country’s border provinces, in its export-led growth model, as well as the infrastructure and development gaps in neighboring regions. Applying a liberal theory perspective, the article finds strong economic support for the initiative in Germany but also growing political concerns about regulatory conflicts over equal market access, Chinese investments in the European Union, and their (potential) political implications for intra-EU decision-making processes. The article concludes that some structural conflicts between the EU/Germany and China are inevitable, as evidenced by the recent launch of the EU’s own infrastructure initiative for Asia – but also that several structural adjustments as well as dwindling Chinese resources will mitigate these conflicts in the future (Asien/GIGA)
Elektronische Reproduktion der Druckausgabe
Keywords: Europäische Union; Deutschland; China